Stakeholder perspectives on graphical tools for visualising student assessment and feedback data - Luciana Dalla Valle; Julian Stander; Karen Gresty; John Eales; Yinghui Wei (Association for Learning Technology, 2018)
This paper contributes to the development of learning and academic analytics in Higher Education (HE) by researching how four graphical visualisation methods can be used to present student assessment and feedback data to five stakeholder groups, including students, external examiners and industrialists. The visualisations and underlying data sets are described, together with the results of a questionnaire designed to elicit the perspectives of the stakeholder groups on the potential value of the visualisations. Key findings of this study are that external examiners agree that the visualisations help them to carry out their role and students concur that they can assist with study organisation, relative performance assessment against the wider cohort and even module choice. All stakeholder groups were positive about the benefits of graphical visualisations in this HE context and supported an increased use of visualisations to assist with data interpretation.